CEO Career Variety: Effects on Firm-Level Strategic and Social Novelty - Crossland, Craig; Zyung, Jinyong; Hiller, Nathan J.; Hambrick, Donald C. (Academy of Management Journal, 2014)
We introduce the concept of “CEO career variety”—defined as the array of distinct professional and institutional experiences an executive has had prior to becoming CEO. Using a longitudinal sample of Fortune 250 CEOs, we hypothesize, and find strong evidence for the assertion, that CEO career variety is positively associated with firm-level strategic novelty—manifested in strategic dynamism (period-on-period change) and strategic distinctiveness (deviance from industry central tendencies). We also find mixed evidence that CEO career variety is positively associated with social novelty—manifested in top management team turnover and heterogeneity.